Embodied Cognition in the Neuro-Sports Learning Model: A Cognitive Intervention Strategy in Elementary School Physical Education - Fauzen, M. Nur Ridwan; Pratama, Fernadiksa Rasta Putra; Pratama, Indra Gunawan (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2025)
This study aims to analyze the application of embodied cognition within the Neuro-Sports Learning (NSL) model as a cognitive intervention strategy in elementary school physical education. The research employed a quasi-experimental, pretest–posttest control-group design, involving two groups: an experimental group receiving instruction through the NSL model based on embodied cognition and a control group engaged in conventional physical education instruction. The participants consisted of 65 elementary school students in Blitar Regency, selected through purposive sampling. Data were collected using the Digit Span Test, D2 Test of Attention, and Cognitive Flexibility Test, and analyzed through t-tests and Repeated Measures ANOVA using SPSS. The findings revealed that the NSL model had a significant effect on enhancing students’ cognitive capacity (p < 0.001) with a large effect size (Cohen’s d = 1.05–1.41). The most significant improvement was observed in working memory and attention, both rated “excellent.” These results demonstrate that integrating embodied cognition principles into the NSL model effectively optimizes brain function by combining structured physical activities with cognitive challenges. The study contributes to the growing body of research on neuroscience-based physical education and provides practical insights into designing cognitively engaging movement-based learning experiences for young learners.